Microstructure and shear property of high-temperature brazing of TiAl alloy and 316L stainless steel with a Ni-based amorphous filler - Guo, Shun; Li, Xiaopeng; Dong, Kewei; Gu, Jieren; Zhou, Qi; Wang, Kehong (Frontiers in Materials, 2022)
High-quality joining of TiAl alloys to stainless steel is of great significance to the aerospace field. However, the hybrid structure of TiAl/316L always suffers from insufficient strength when serving at elevated temperatures. In this work, a high-melting-point quaternary Ni-Nb-Zr-Ti amorphous alloy was applied as the filler metal to braze the two alloys at different temperatures. The microstructure and mechanical properties were studied in detail, and the results indicated that the joint was divided into three different regions and various reaction products were formed after brazing. The shear strength of the joint tends to first increase and then decrease with increasing brazing temperature. A satisfactory joint was obtained at 1090℃, and the highest shear strength reached 290 MPa and 180 MPa at room temperature and 750℃, respectively. Shear fracture indicates that there were obvious cleavage steps and some secondary cracks on the fracture surface, indicating that a high-melting-point quaternary Ni-Nb-Zr-Ti amorphous alloy is useful to improve the bonding strength of TiAl alloy and 316L stainless steel, but it is difficult to effectively improve the plasticity. The fracture occurred on the TiAl interfacial region, and the phase causing microcrack initiation and propagation was AlNiTi.